2018
DOI: 10.1007/s11244-018-0893-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mass Transport on the Electrochemical Oxidation of Alcohols Over Electrodeposited Film and Carbon-Supported Pt Electrodes

Abstract: Electrochemical oxidation of four different alcohol molecules (methanol, ethanol, n-butanol and 2-butanol) at electrodeposited Pt film and carbon-supported Pt catalyst film electrodes, as well as the effect of mass transport on the oxidation reaction, has been studied systematically using the rotating disk electrode (RDE) technique. It was shown that oxidation current decreased with an increase in the rotation rate (ω) for all alcohols studied over electrodeposited Pt film electrodes. In contrast, the oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 63 publications
1
29
0
2
Order By: Relevance
“…However, in real electrochemical applications (fuel cells or electrochemical convertors), the alcohol is supplied to the anode electrode, that is, the system is under hydrodynamic conditions. It is thus important to take into account the effect of fuel transport to the catalyst [21] and the transfer of byproducts through the catalyst layer.…”
Section: Ch3ch2oh + 3 H2o → 2 Co2 + 12 H + + 12 E −mentioning
confidence: 99%
“…However, in real electrochemical applications (fuel cells or electrochemical convertors), the alcohol is supplied to the anode electrode, that is, the system is under hydrodynamic conditions. It is thus important to take into account the effect of fuel transport to the catalyst [21] and the transfer of byproducts through the catalyst layer.…”
Section: Ch3ch2oh + 3 H2o → 2 Co2 + 12 H + + 12 E −mentioning
confidence: 99%
“…Ethanol has been electrochemically oxidized in basic media to several products including acetate, acetylaldehyde, and CO2. [28][29][30] To determine the extent to which ethanol could be oxidized to any of these products, a control experiment was performed by spiking the anolyte with 1000 ppm ethanol with bulk electrolysis performed under N2 flow. Figure 4a shows a schematic illustration of the vapor-fed testbed in Multi-physics modeling, with the calculation domain of the 2D model for water-vapor transport available in the Supporting Information file.…”
mentioning
confidence: 99%
“…Similar results to formic acid oxidation were seen that the peak currents of methanol oxidation decreased with the increase in the rotating speed. The decrease indicates that the reaction is not mass transport controlled and suggests increased diffusion of reactive species away from the electrode surface with the increase of the rotating speed [14]. Seland et al showed that the current density of methanol oxidation is decreasing as a function of rotating rate both in the positive-going scan and the negative-going scan [15].…”
Section: Resultsmentioning
confidence: 99%